Stereospecificity of the Hofmann elimination in the gas phase. Issue 1 (February 2018) - Figadére, Bruno; Cao, Tangyuan; Morton, Thomas H
The Hofmann elimination of ammonium ions having a single positive charge is demonstrated to exhibit stereospecificity with regard to expulsion of neutral alkene. For the 3-hexyl series of threo and erythro 4-monodeuterated ions (3-hexylammonium ion; N, N, N- trimethyl- d 3 -3-hexylammonium ion; N- ethyl-3-hexylammonium ion; N- methyl, N- ethyl-3-hexylammonium ion; N, N- dimethyl, N- ethyl-3-hexylammonium ion), the upper limit of the E:Z ratio of the expelled alkene (r) approaches 2 (the stereospecificity) with a deuterium isotope effect close to 2.0, although the effects of isotopic substitution diminish the E:Z ratio somewhat. Two fragmentations compete with that reaction: hydride shift (which gives the same products but with hydrogen scrambling) and loss of a neutral amine to give an alkyl cation. These competing reactions render our calculation approximate, but the results suggest a value not too far from the upper limit.